Opposition in authoritarian regimes – a case study of Russian non-systemic opposition - Nadskakuła-Kaczmarek, Olga (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2017)
According to Juan Linz, authoritarian rulers permit limited, powerless political pluralism and organization of elections, but they make it very clear that a change in power is impossible and the opposition cannot take over. Elections in authoritarian regimes are a part of nominally democratic institutions and help rulers to legitimize the regime. They are not free or fair, and therefore do not present any opportunity for the opposition to win and change the political system afterward. The question could be asked, what kind of action the opposition should undertake in order to improve its strength. That is the main problem nowadays for non-systemic opposition in the Russian Federation. On the one hand, the opposition has a problem gaining access to elections, but on the other hand, it knows that even if it could take part, the elections would not be democratic. This article tries to shed light on the strategies of the non-systemic Russian opposition and the possibility of its impact on Russian society when the government tries to marginalize, weaken and eventually destroy the non-systemic opposition.

Według Juana Linza, autorytarni władcy dopuszczają ograniczony i bezsilny pluralizm polityczny i organizację wyborów, ale jasno pokazują, że zmiana władzy jest niemożliwa, a opozycja nie może przejąć władzy. Wybory w reżimach autorytarnych są częścią nominalnie demokratycznych instytucji i pomagają władzom legitymizować panujący reżim. Wybory nie są wolne ani uczciwe, a zatem nie stanowią szansy dla opozycji, aby wygrać i zmienić system polityczny w ich następstwie. Można zadać pytanie, jakiego rodzaju działania powinna podjąć opozycja w celu wzmocnienia swojej pozycji. Jest to obecnie główny problem niesystemowej opozycji w Federacji Rosyjskiej. Z jednej strony ma ona problem z uzyskaniem dostępu do wyborów, ale z drugiej strony wie, że nawet gdyby mogła wziąć w nich udział, nie byłyby to wybory demokratyczne. Artykuł stara się rzucić światło na strategie niesystemowej opozycji rosyjskiej i możliwości jej wpływu na rosyjskie społeczeństwo, w warunkach gdy rząd próbuje marginalizować, osłabiać i ostatecznie niszczyć niesystemową opozycję. Artykuł przedstawia krytyczną analizę literatury i dokumentów na ten temat.
Opozycja w reżimach autorytarnych – stadium przypadku na przykładzie rosyjskiej opozycji niesystemowej
Keywords: non-systemic opposition; authoritarianism; Kremlin; protest movement; niesystemowa opozycja; autorytaryzm; Kreml; ruch protestacyjny